The Diversity of Butterflies (Order: Lepidoptera) in Pondok Ambung, Tanjung Puting National Park, Kalimantan Tengah - Astuti, Ari Nidhi; R.C. Hidayat Soesilohadi; Sukirno, Sukirno; Andhika Puspito Nugroho; Siti Sumarmi (Jurnal Biologi Tropis, 2024)
National parks are one of a site to maintain biodiversity from any damage. Tanjung Puting National Park is one of the national parks in Indonesia with a wide variety of biodiversity, namely butterflies. The aims of this study were to determine the diversity of butterfly species in 5 sub-ecosystems in Tanjung Puting National Park. The five sub-ecosystems are Camp Ambung, post-burn forest, heath forest, lowland forest and swamp forest. In this study, the butterflies were caught through the hunting method by using insect nets and the trapping method by installing food traps. This study was conducted from February to March 2022 for twice times a day from 8 to 12 in the morning and 1 to 5 in the afternoon. The results showed that butterflies collected were 121 species of butterflies from 6 families in Pondok Ambung, Tanjung Puting National Park. In detail, there were 88 species in Camp Ambung, 19 species in the post-burn forest, 14 species in the heath forest, 65 species in the lowland forest, and 38 species in the swamp forest. The diversity index from highest to lowest was Camp Ambung (3.71), lowland forest (3.49), swamp forest (3.02), post-burn forest (2.61), and heath forest (2.36).